2009
DOI: 10.1007/s00436-009-1686-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Neospora caninum, Hammondia sp., and Toxoplasma gondii in tissues from slaughtered beef cattle in Bahia, Brazil

Abstract: Neospora caninum, Hammondia sp., and Toxoplasma gondii are parasites with morphological and genetic similarities. N. caninum and T. gondii are important abortive agents of cattle and sheep, respectively, and may infect numerous animal species. Hammondia sp. is not known to induce disease in animals, but may cause confusion in the identification of closely related coccidia. The aim of this study was to investigate infection rates caused by N. caninum, Hammondia sp., and T. gondii in beef cattle using a nested P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
3
28
2
6
Order By: Relevance
“…Interesting the fact that Garcia et al (1999), Ogawa et al (2005), that worked with animals from northern Paraná state, found 25.8% and 26%, and Santos et al (2010) that studied cattle from Bahia found 26% of serum prevalence of antibodies, which were similar than observed for us in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Interesting the fact that Garcia et al (1999), Ogawa et al (2005), that worked with animals from northern Paraná state, found 25.8% and 26%, and Santos et al (2010) that studied cattle from Bahia found 26% of serum prevalence of antibodies, which were similar than observed for us in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the presence of T. gondii has been confirmed in beef cattle in Brazil by serological studies (GarCia et al, 1999), PCR and sequencing (sanTos et al, 2010), and isolation by bioassay (maCeDo et al, 2012), the present investigation performed in aborted fetuses with lesions indicative of protozoal infection were negative for T. gondii DNA, in accordance to studies performed in many countries, where the rate of infected bovine fetus with T. gondii was low (Dubey, 1986).…”
Section: Palavras-chavesupporting
confidence: 88%
“…The gene region ITS-1 has become the target for phylogenetic studies, since this region experiences greatest mutagenic evolutionary pressure and is subject to polymorphism (PAYNE and ELLIS, 1996;AL-QASSAB et al, 2009;AL-QASSAB et al, 2010;SANTOS et al, 2010). Despite these studies, there are still few gene sequences of ITS-1 deposited in GenBank, including those originating from Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic investigations on N. caninum contribute towards expanding the knowledge of the characteristics and behavior of samples of the parasite in Brazil (SANTOS et al, 2010). The gene region ITS-1 has become the target for phylogenetic studies, since this region experiences greatest mutagenic evolutionary pressure and is subject to polymorphism (PAYNE and ELLIS, 1996;AL-QASSAB et al, 2009;AL-QASSAB et al, 2010;SANTOS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%